2014
DOI: 10.1016/j.molcel.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Histone-Fold Domain Protein NF-Y Promotes Chromatin Accessibility for Cell Type-Specific Master Transcription Factors

Abstract: SUMMARY Cell type-specific master transcription factors (TFs) play vital roles in defining cell identity and function. However, the roles ubiquitous factors play in the specification of cell identity remain underappreciated. Here we show that the ubiquitous CCAAT-binding NF-Y complex is required for the maintenance of embryonic stem cell (ESC) identity and is an essential component of the core pluripotency network. Genome-wide studies in ESCs and neurons reveal that not only does NF-Y regulate genes with house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
203
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(213 citation statements)
references
References 49 publications
9
203
0
1
Order By: Relevance
“…In the NF-Y trimeric complex, the NF-YA subunit is involved in the specific recognition and binding of the CCAAT box, but can only achieve this binding in the presence of the unrelated NF-YB and NF-YC proteins, which contain histone fold motifs. These deviant histone proteins are involved in promoting chromatin accessibility to NF-YA and other specific TFs, as well as the recruitment of additional interacting proteins (Nardini et al, 2013;Oldfield et al, 2014). In animal cells, each subunit is encoded by a single gene, and their molecular assembly has been well characterized: whereas the NF-YA subunit with its nuclear localization signals is targeted to the nucleus, the NF-YB and NF-YC subunits first form a dimer in the cytoplasm, before being transported to the nucleus to form a heterotrimer with NF-YA that binds to the CCAAT box (Mantovani, 1999).…”
mentioning
confidence: 99%
“…In the NF-Y trimeric complex, the NF-YA subunit is involved in the specific recognition and binding of the CCAAT box, but can only achieve this binding in the presence of the unrelated NF-YB and NF-YC proteins, which contain histone fold motifs. These deviant histone proteins are involved in promoting chromatin accessibility to NF-YA and other specific TFs, as well as the recruitment of additional interacting proteins (Nardini et al, 2013;Oldfield et al, 2014). In animal cells, each subunit is encoded by a single gene, and their molecular assembly has been well characterized: whereas the NF-YA subunit with its nuclear localization signals is targeted to the nucleus, the NF-YB and NF-YC subunits first form a dimer in the cytoplasm, before being transported to the nucleus to form a heterotrimer with NF-YA that binds to the CCAAT box (Mantovani, 1999).…”
mentioning
confidence: 99%
“…However, we provide biochemical evidence that the trimer is a much more efficient DNA binding entity in vitro, and a physiological one in vivo, as the matrices of the HFD mutants resemble those of co. The HFD importance could be linked to their histonelike nature, as they might play the known "pioneer" role of NF-Y in penetration of chromatin territories devoid of positive histone marks (Fleming et al, 2013;Oldfield et al, 2014;Sherwood et al, 2014;Lu et al, 2016).…”
Section: Lessons About Nf-co From the Nf-y/ccaat Structurementioning
confidence: 86%
“…The targeted DNA sequence is the CCAAT box, originally discovered in human promoters, and later found in all eukaryotes. Mechanistically, different experiments in the mammalian system suggested that the CCAAT box and NF-Y serve a "pioneering" role in gene activation, namely, that this TF is able to penetrate "hostile" chromatin territories and set the stage for binding of other TFs required for full gene activation (Fleming et al, 2013;Sherwood et al, 2014;Oldfield et al, 2014). This hypothesis is further supported by recent experiments with mouse zygotes, where NF-Y appears to be the major TF opening chromatin as early as the two-and four-cell stages (Lu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The TFs considered in this study included pioneer factors from different TF families, including GATA2 from the GATA family (Anguita et al 2002), NFYB (Oldfield et al 2014) from the NFY family, SPI1 from the ETS family (Wang et al 2014), and RFX5 from the family of RFX-related factors (Gauthier et al 2012). …”
Section: Hm Patterns Surrounding Tf Bss and Non-bss Show Conserved Pamentioning
confidence: 99%